Perlindungan Hukum Bagi Anak Berkonflik Dengan Hukum Dalam Tindak Pidana Pencurian Dengan Kekerasan (Studi Putusan Nomor 2/Pid.Sus-Anak/2021/PN.Bks) - Putra, Joshua Aldo Tri; Apriyani, Maria Novita (Lex Stricta : Jurnal Ilmu Hukum, 2026)
Child protection within the Indonesian legal system constitutes a state obligation, particularly for children in conflict with the law, as they have not yet reached the psychological and social maturity of adults. This study aims to identify the forms of legal protection available to child victims of violent theft and to analyze the application of relevant legal provisions in Decision Number 2/Pid.Sus-Anak/2021/PN Bks. The research employs a normative juridical method using statutory and case approaches, supported by an examination of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System and relevant observations through online legal sources. The findings show that legal protection for children in the decision is manifested through two principal forms, namely preventive and repressive protection. These two forms complement each other in ensuring the fulfillment of children’s rights and humane treatment, so that the imposition of rehabilitation in the Special Development Institution for Children remains grounded in the best interests of the child.